Descriptive statistics and rainfall anomaly index in the composition of studies of rainfall and environmental sanitation in the municipality of Pindoretama – CE - Lima , Tiago de Abreu; Aderaldo, Pedro Ítalo Carvalho; Aderaldo, Francisco Ícaro Carvalho; Gino, Guilherme Façanha; Almeida, João Roberto Façanha de (Technical and Scientific Journal Green Cities, 2024)
The distribution of rainfall is an important parameter for determining social welfare, for the development of economic activities and in the planning of infrastructure of a municipality. In addition, the constant study of municipal rainfall is extremely relevant, especially in regions where its distributions are irregular, such as in the Northeast Region of Brazil. Therefore, the present work aimed to carry out a study of the rainfall in the municipality of Pindoretama – CE through descriptive statistics and the Rainfall Anomaly Index (IAC), using the historical series from 1994 to 2023 as a reference. Among the results obtained, it was verified the performance of climatic phenomena for the municipality that interfere in the local precipitation, in addition, the behavior of the monthly rainfall for these years was analyzed, also corroborating the studies so that short, medium and long term data are available. Therefore, through this work, it was verified how relevant the tools of descriptive statistics and IAC are in the studies of rainfall, in the promotion of studies related to municipal environmental sanitation.